Church, Cinema, and their Representational Role of Prophet Jesus, With Mary Magdalene: In the Context of Qur’ān, Bible and Historical Facts - Muhammad Asad Latif (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
Respecting the Prophets is necessary in every religion and desecrating them is punishable. In 1895 Skladanowsky Bros, started the era of filmography, and after two months Lumiere bros as well, but they didn’t get the well audience. The dramatic irony continued, and they started the filming of Jesus and showing his miracles on screens and theaters, then they got their goals and aims. Time to time western cinema showed his personality as married, as gay and as nudist Prophet, which is not only against Islamic sharīʿah and faith but its Christian religion either. In Islamic point of view, it’s offensive pictorial scenario of the past whole history. In this essay will show out those superstitions and figures out.